The quality of life of seniors from Romania during the coronavirus pandemic period - Chirugu, Gianina; Rus, Mihaela; Rus, Ciprian-Vasile (Technium Social Sciences Journal, 2022)
This paper presents a pilot study conducted at the national level of Romania, which has as main objective the analysis of the quality of life of elderly people during the pandemic period. The sociological survey based on self-administered questionnaire was established as a research method, and for the data collection was developed the working tool adapted to the older people’s quality of life (OPQOL) questionnaire model. In order to have a clear picture of the quality of life of elderly people in Romania during the pandemic period, the following indicators were used in the analysis of the quality of life of elderly people: the status of beneficiary of social services, gender of the elderly, the geographical area in which the elderly person lives, the degree of satisfaction of the quality of life of the elderly, the impact of the pandemic on the lifestyle of the elderly. The participation of elderly people in the study was voluntary and their responses are confidential and are used exclusively for scientific purposes. The questionnaire has three parts, the first being dedicated to a general question, the second part contains 13 closed questions and the last part includes socio-demographic variables regarding the elderly participants in the research are cumulative for the whole sample both for those benefiting from social services, and for those who are not in the records of an institution providing social services. The research involved 306 elderly people aged between 61 and 99 years, the gender of the respondents participating in the research is mostly female, and the living environment is mostly urban and one third of the elderly people participating in the pilot study live alone. The two hypotheses from which quantitative research was based have been confirmed.